Annual report: 1972-1973 - Cocoa Research Institute (Ghana: Cocoa Research Institute, 1975)
The book contains the report of the activities of Cocoa Research Institute of Ghana for the period of 1972-1973.
Includes index
usc 13/02/2019
Loans
Keywords: Cocoa; Cocoa-Research; Ghana